The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.24926/ijps.v3i1.122
|View full text |Cite
|
Sign up to set email alerts
|

Improving Interdisciplinary Relationships in Primary Care with the Implementation of TeamSTEPPS

Abstract: A major challenge in healthcare is lack of interdisciplinary collaboration (O’Daniel & Rosenstein, 2008). The Institute of Medicine report, To Err is Human: Building a Safer Health System (1999), shows that errors often occur due to lapses in partnership and communication. This article describes the implementation of TeamSTEPPS, an evidence-based tool for optimizing staff relationships and partnership, in a clinic in which a change in the care model had affected interprofessional collaboration and teamwork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Our study findings are consistent with other studies in acute care settings. 9,[27][28][29][30][31][32] Less research has been done targeting these concepts in nursing homes. Work has shown that team effectiveness and relational coordination are influential on patient outcomes and staff satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings are consistent with other studies in acute care settings. 9,[27][28][29][30][31][32] Less research has been done targeting these concepts in nursing homes. Work has shown that team effectiveness and relational coordination are influential on patient outcomes and staff satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…TeamSTEPPS interventions have a significant impact and last a long time in team orientation. (Siddons et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The targeted content was related to task-specific frames of references when existing (Table 3). [24][25][26] While the targeted content grid for Interprofessional collaboration included the same dimensions as the communication one, the targeted content grid for the physical exam and technical procedure was slightly modified to incorporate a dimension about the precision/accuracy of the procedure and two different dimensions related to communication (communication addressing the clinical facts and communication addressing patient comfort and emotions) in addition to the structure dimension.…”
Section: Development Of a Generic Feedback Content Gridmentioning
confidence: 99%